Germination and Heat Resistance of Parageobacillus and Geobacillus spp. Spores - Maika Salvador; Santiago Condón; Elisa Gayán (Foods, 2025)
Geobacillus and Parageobacillus spores are major spoilage agents in thermally treated, shelf-stable foods, particularly milk products, due to their high heat resistance. This study aimed to investigate how spore purification, maturation time, and sporulation temperature influence the germination and heat resistance of P. thermoglucosidasius, G. thermodenitrificans, and G. stearothermophilus spores, with the goal of improving the reliability of microbial risk assessment. All three species germinate efficiently in milk, likely triggered by lactose and glucose. Ethanol-treated spores during purification germinated without heat activation, while water-washed spores required it. At least four days of maturation were needed for efficient germination, though extending maturation to seven days led to strain-dependent changes in heat resistance: it increased in G. thermodenitrificans, decreased in P. thermoglucosidasius, and remained stable in G. stearothermophilus. Sporulation at 55 °C consistently favored germination at the same revival temperature. G. stearothermophilus reached the highest heat resistance at 55 °C, whereas the other species were more resistant when sporulated at 60 °C. These findings underscore the importance of standardizing spore-preparation protocols, as key parameters such as purification, maturation time, and sporulation temperature critically affect spore properties relevant to food stability.